1970
DOI: 10.1210/endo-86-1-88
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Proinsulin to Insulin Conversion in Isolated Rat Islets

Abstract: By pulse labeling isolated rat islets with tritiated leucine, it was possible to follow the synthesis of proinsulin and the subsequent conversion of the proinsulin into an intermediate product and insulin. Examination of the islets fractionated at various times indicated synthesis of proinsulin in the microsomal fraction and transfer of the proinsulin to the secretion granule fraction. The secretion, granule fraction was the most important fraction in converting proinsulin to the intermediate product and insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1970
1970
1996
1996

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Although radioautographic studies on the biosynthesis and transfer of secretory products in a wide variety of cells strongly support the hypothesis that the secretory products are confined within the cell to the rough endoplasmic reticulum, Golgi apparatus and, finally, to the secretion granules (6,7,(20)(21)(22), even more definitive proof of this strict compartmentation has been obtained in some instances by histochemical localization techniques (23). On the other hand, fractionation studies with disrupted cells have never succeeded in demonstrating this degree of sequestration (4,24), presumably due to the fragility of some of the subcellular membranous structures, which release their contents during homogenization of the tissue. We might then first inquire as to whether evidence was obtained in these experiments for the existence of alternate or nongranule routes of insulin secretion from the islets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although radioautographic studies on the biosynthesis and transfer of secretory products in a wide variety of cells strongly support the hypothesis that the secretory products are confined within the cell to the rough endoplasmic reticulum, Golgi apparatus and, finally, to the secretion granules (6,7,(20)(21)(22), even more definitive proof of this strict compartmentation has been obtained in some instances by histochemical localization techniques (23). On the other hand, fractionation studies with disrupted cells have never succeeded in demonstrating this degree of sequestration (4,24), presumably due to the fragility of some of the subcellular membranous structures, which release their contents during homogenization of the tissue. We might then first inquire as to whether evidence was obtained in these experiments for the existence of alternate or nongranule routes of insulin secretion from the islets.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the biosynthesis of insulin in intact islets of Langerhans isolated from rat pancreas have shown that single chain proinsulin is synthesized in the rough endoplasmic reticulum, presumably on membrane-bound polyribosomes, and is subsequently transformed within the islet cells to insulin, the principal storage product of the beta granules (1)(2)(3)(4). The subcellular site of transformation of proinsulin to insulin has been localized tentatively to the Golgi apparatus and/or the newly formed secretory granules (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…A 1-ml aliquot of the homogenate was removed; the remaining suspension was carried through differential centrifugation to obtain subcellular fractions. The speeds and times for centrifugation were identical to those we have used with islet tissue to obtain a secretion granule fraction (2). The conditions are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Sorensen et al 27 have recently presented evidence supporting this hypothesis based on the distribution of labeled proinsulin and insulin in islet subcellular fractions. Such a mechanism would account for the retention of all of the proteolytic conversion products.…”
mentioning
confidence: 90%